Palavras lusófonas na Comparative Political Theory | Lusophone words in Comparative Political Theory - Favarato, Claudia (2021)
The discipline of comparative political theory (CPT) rose within the Anglo-Saxon context in the 1990s; rejecting the existing epistemological hegemony, it aims to integrate non-western theories and thought in political theory. Following a brief overview of CPT, this paper intends to report that CPT in nigh existent in the scholarship of political theory available in Portuguese. The overall scarcity of CPT in Portuguese scholarship texts epitomizes not only the lack of response to comprehensive, globalized or cosmopolitan canons of political theory, as referred in anglophone literature, but also a failure in providing space and representation for authors, texts, ideas and concepts beyond the canons. Among the areas of interests of CPT, political theorizations endogenous of Africa are the least considered ones. In the Portuguese literature of political theory, sub-Saharan and Luso-African political thought and theory are underrepresented.